Show the BET N2 adsorption/desorption isotherm for calculating the surface area of Fe3O4 (a), and the XRD pattern of Fe3O4 (b). - Tamer S. Saleh (5181146) (2025)
Show the BET N2 adsorption/desorption isotherm for calculating the surface area of Fe3O4 (a), and the XRD pattern of Fe3O4 (b).